THE THEORY OF THE SEPARATION OF POWERS, THE DEVELOPMENT PROCESS AND ITS APPLICATION TODAYABSTRACT - Körbayram, Azam (International Scientific Journal Vision, 2022)
The guarantee of freedoms can be only in liberties and democratic states. In particular, the states based on the start of the constitutionalist movements and the provisions of the 1789 French Declaration have to build their modern states on the axis of the theory of separation of powers. Although it was Locke and Montesquieu who systematized the theory of separation of powers, it is certain that the contribution of medieval thinkers on this issue could not be underestimated until the modern age. In fact, the number of those who state that the theory of separation of powers of many thinkers is based on the ancient Greek philosophers and that the starting point goes back to ancient times is not to be underestimated. However, at the time it was systematized, the question comes to mind, is it the same as the predicted form and the one used today? In the period when the theory was systematized, there was no such thing as a political party, especially in Western Europe, and in the thoughts of the jurists, the monarch, who held all power, had a struggle to increase the effectiveness of the parliaments, which are the representatives of the people, against this power, and to establish a balance system against the arbitrary rule of the monarch. Of course, with the emergence of political parties over time and having an effective role in the state order, it is striking that it turned into a form of conflict between the ruling party with the majority votes and the opposition party bloc remaining in the minority. In this article, although it is important how the separation of powers theory was in previous ages and whether there is a difference in understanding and use today, I think it is a subject that needs to be examined. The article aims to analyze the current situation by examining the ideas of medieval and modern age thinkers, starting with the views of ancient thinkers about this theory.